Liver Health and Dementia in an Italian Older Population: Findings From the Salus in Apulia Study - Lampignano, Luisa; Donghia, Rossella; Griseta, Chiara; Lagravinese, Gianvito; Sciarra, Sabrina; Zupo, Roberta; Castellana, Fabio; Bortone, Ilaria; Guerra, Vito; Tirelli, Sarah; De Nucci, Sara; Tatoli, Rossella; et al. (Frontiers in Aging Neuroscience, 2021)
Objectives: Non-alcoholic fatty liver disease (NAFLD) currently affects a quarter of the global population. Systemic inflammation, metabolic syndrome, and coronary artery disease, all conditions associated with NAFLD, have also been related to cognitive dysfunction in older age. The present study aimed to investigate the relationship between NAFLD risk and a dementia diagnosis in a large population-based sample aged >65 years. Methods: We selected 1542 participants (723 men) from the Salus in Apulia Study. To assess the risk of fat distribution in the liver, we used the Fatty Liver Index (FLI). Dementia was diagnosed according to the American Psychiatric Association criteria (DSM-5). Results: The overall prevalence of dementia was 8.5% [95% confidence interval (CI): 7% to 10%]. Subjects with dementia were older (effect size (ES): -0.89, 95% CI: -1.07 to -0.70), had a lower level of education (ES:0.88, 95% CI:0.69 to 1.06), higher levels of gamma-glutamyl transferase (ES: -0.21, 95% CI: -0.39 to -0.03), lower levels of total cholesterol (ES -0.24, 95% CI: -0.42 to -0.06) and low-density lipoprotein cholesterol (ES: -0.20, 95% CI: -0.38 to 0.02) and a higher FLI (ES: -0.22, 95% C.I.: -0.39 to -0.04). In the logistic regression model adjusted for age, sex, education, hypertension, diabetes mellitus, alcohol consumption, smoking habits, and stroke, a dementia diagnosis was positively associated with FLI >60 (odds ratio:1.83, 95% CI:1.04 to 3.24). Conclusion: Our findings suggested that an increased NAFLD risk may be associated to dementia and cognitive decline in older age. Considering the high NAFLD prevalence, the possible adverse disease effects on cognitive performance pose a health problem with significant social and economic implications.